(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Viral diarrhea remains a significant public health challenge worldwide, especially among children under five years of age. Despite advancements in diagnostic technologies and vaccination efforts, viral gastroenteritis caused by rotavirus, norovirus, adenovirus, and astrovirus continues to contribute to high morbidity and mortality rates, particularly in low- and middle-income countries. This review highlights the current epidemiological trends, diagnostic difficulties, and preventive strategies associated with viral diarrhea, emphasizing the need for integrated surveillance systems, improved sanitation, and global access to vaccination